Future of e-Learning in Medical Education—Perception, Readiness, and Challenges in a Developing Country - Syed, Sabin; Rastogi, Aayushi; Bansal, Akanksha; Kumar, Ashish; Jindal, Ankur; Prakash, Arun; Agarwal, Gaurav; Varshney, Mohit (Frontiers in Education, 2021)
BACKGROUND - Medical Institutes in India and globally, were widely affected by COVID-19 pandemic and there was an almost immediate need to extemporize modules to be adjusted in order to deliver through e–learning platforms. This study was undertaken to gage the future and usefulness of e-learning in the medical education by analysing the perception, attitude and readiness of healthcare learners during the ongoing pandemic.' METHODOLOGY- A quantitative survey was conducted among healthcare community, especially during lockdown. A survey questionnaire was developed to understand the demographic details, knowledge, infrastructure access and attitude of the healthcare professionals. It was circulated through snow-balling technique with one hundred healthcare and allied professionals (linked with Project ILBS-ECHO) as the initial seeds. Each person was asked to then circulate the survey to 20 or more of their contacts and so on till the proposed duration of the study. Identifying information was anonymised before and ethical approval was obtained prior to initiating the survey. RESULTS- A total of 3004 healthcare professionals voluntarily participated in the survey. The respondents were mostly young adults, with 61% of participants being <30 years of age. About 65.41% used e-learning platforms for obtaining knowledge and skills during pandemic, despite 71.1% of the respondent reporting cyber security concerns. Significant payback of e-learning mentioned by participants was reduction in travel time and assistance in maintaining social distancing (68.21%) without compromising the learning. CONCLUSION- With learners incessantly jumping on to the bandwagon, the trend can be anticipated to continue post pandemic. For this reason, the study tried to highlight the awareness, perceptions and potential challenges faced by Indian healthcare and allied professionals, regarding e-learning as a method of education.